In vivo performance of injectable self-hardened synthetic bone cement (osteopaste) as a filler for bone defects - Zulkifly, Ahmad Hafiz; Zakaria@Mohamad, Zamzuri; Che Seman, Che Nor Zarida; Awang, Mohd Shukrimi; Mohd Yusof, Nazri; Che Ahmad, Aminudin; Buyong, Zunariah; Fazan, Fazilah (2019)
A new injectable self-hardened synthetic bone cement (Ostepaste) was developed for filling bone defects. The major component of Osteopaste was limestone which consisted of tetra-calcium phosphate (TTCP) and tri-calcium phosphate (TCP) powder. Osteopaste showed good potential for clinical applications as it was shown biocompatible, osteoconductive and osteointegration.